Voltammetry of Ferrocenated Gold Nanoparticles on a Nanometer‐Sized Electrode. Issue 5 (15th April 2014) - Sun, Peng; Sun, Tong; Anz, Samir; Corey, Jason; Tan, Yunshi
Abstract So far, almost all electrochemistry theories are based on an assumption that the size of an electroactive molecule is negligible. However, this assumption will not be true if the size of an electroactive molecule is comparable to or smaller than the size of an electrode being used to study the electroactive molecule. In this paper, the electrochemical behaviors of ferrocenated gold nanoparticles have been studied using an electrode with a radius that is smaller than the radius of the particle. This allows for the observation of phenomena which cannot be explained by conventional electrochemical theories. Also, stochastic collision current, which cannot be observed on a macro‐ or microelectrode, can be directly observed.